(untitled) (Revista Contexto & Educação, 2020)
This paper is the result of a qualitative state-of-the-art research, which aimed to search for theses and dissertations that dealt with the curricular integration in the Federal Institutes (FIs), focusing on integrated high school (IHS). A search at the Digital Library of Theses and Dissertations (DLTD) was conducted, which resulted in thirteen analyzed studies. In parallel, we elaborated the profile of these researchers, through a consultation on the Lattes platform. The research has shown that studies on curricular integration within the scope of the HIS of the FIs show the distancing of what is wanted for the IHS from what is done. It is possible to realize the concern with the theme, however the investigations do not point out practical suggestions for the materialization of the integrated curriculum.